Is risk aversion related to occupational choice: evidence from 1996 PSID. Issue 10 (7th June 2021) - Zhao, Zhiqi; Zhou, Guangyou
ABSTRACT: This paper investigates to what extent individuals' risk aversion are correlated with the choice of occupation which differs from earnings risk by using 1996 PSID. Following Kimball et al. (2009), we first impute the individuals' coefficient of relative risk aversion based on personal characteristics. Then, on the aggregate level, we find workers who are more risk averse will sort into occupations with low earnings risk. On the individual level, for one-unit increase in the coefficient of relative risk aversion, the probability of going to a more risky occupation decreases by 13.5%.